The Evaluation of CD10 and HER2 Immunohistochemical Markers in Urothelial Carcinoma of Urinary Bladder - Khalid W. Abdulfattah Khattab; Nadwa Subhi Alazzo; Banan Burhan Mohammed (Medical Journal of Babylon)
Background: Urothelial carcinoma (UC) has been considered the most frequent bladder tumor. Although the degree of bladder wall invasion and grade of the tumor are the essential prognostic factors in bladder carcinoma, there is no dependable parameter predicting patients’ outcomes. Objectives: To assess the frequency of CD10 expression (in tumor cells and tumor stroma) and HER2 (in tumor cells) in primary UC of the urinary bladder and to assess their relation with patients’ age, gender, grade, lympho-vascular invasion, and muscle invasion. Materials and Methods: In this retrospective case series study, 50 cases of primary bladder UC were obtained through a transurethral resection, and a study for CD10 and HER2 was done by immunohistochemical (IHC) technique. Results: The age of patients ranged from 34 to 90 years (mean = 59.9 years) with male to female ratio was 7.33:1. CD10 expression in tumor cells was positive in 60% of cases while in the stromal cells, it was only positive in 38% of the cases. HER2 IHC stain was positive in 20 cases (40%). A significant association was detected between stromal CD10 expression with the gender of patients, tumor grade, and muscle invasion (P = 0.0244, P = 0.004115, and P = 0.0378, respectively). HER2 IHC stain showed a significantly higher expression in higher grade and muscle invasion cases (P = 0.00875 and P = 0.0445, respectively). No significant association was detected between tumorous CD10 expression and any clinicopathological parameters. Conclusion: CD10 expression in stromal cells (not in tumor cells) and HER2 IHC stain can be used as prognostic markers in primary bladder UC.